DIRASAH AL-USLUB WA AL-USLUBIYAH FI NAQD AL-ARABY - Ibrahim Ali, Habibullah Ali (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2015)
In this study, we addressed method and style in Arabic criticism. By the efforts of Arab critics of old and new issue, the subjects of study were as follows: First, the stylistic origins. It means a stylistic in linguistic and rhetoric and literary criticism and other related; Second, analysis of stylistic levels where we focus on stylistic study premises for literary texts; Third, a study of the method in the old Arab criticism, in this part of the study, we noted some efforts by Arab critics about stylistic and their relevance studies in this stylistic aspect; Fourth, the stylistic of contemporary Arab criticism. This aspect of the survey stood at some critics of contemporary Arab studies in Stylistics, as stated what distinguishes each study than other studies. It is included as an appendix in whale most important results achieved in this study.